2016
DOI: 10.1007/s00414-016-1488-z
|View full text |Cite
|
Sign up to set email alerts
|

Sex estimation from the long bones of modern South Africans

Abstract: Best scientific practice for sex estimation incorporates accurate techniques that employ appropriate standards and population- and period-specific data. Single measurements provide accurate sex estimations, but multiple measurements and multivariate techniques offer greater validity to biological profile assessments. Appropriate, modern standards for sex estimation are limited to the cranium in South Africans (SA), which warrants the examination of the potential for sex estimation using the postcrania of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…Specifically, employing FDA or logistic regression with a large number of predictor variables (i.e., multiple variable subsets), an anthropologist can estimate sex from the long bones, or a combination of, for individuals between birth and 12 years up to 93% bootstrapped accuracy. The bootstrapped accuracies of the multiple variable subsets are comparable to results using morphological indicators of the pelvis and metric variables of the postcrania for adults (Klales, Ousley, & Vollner, ; Krüger, L'abbe, & Stull, ; Spradley & Jantz, ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Specifically, employing FDA or logistic regression with a large number of predictor variables (i.e., multiple variable subsets), an anthropologist can estimate sex from the long bones, or a combination of, for individuals between birth and 12 years up to 93% bootstrapped accuracy. The bootstrapped accuracies of the multiple variable subsets are comparable to results using morphological indicators of the pelvis and metric variables of the postcrania for adults (Klales, Ousley, & Vollner, ; Krüger, L'abbe, & Stull, ; Spradley & Jantz, ).…”
Section: Discussionmentioning
confidence: 56%
“…Proximal and distal breadth measurements (i.e., FDB, TPB, HDB, HPB and TDB) were consistently recognized as important measurements in model creation. Similar measurements produce the highest classification accuracies in adult sex estimation (Krüger et al, ; Spradley & Jantz, ). While previous research did not find any significant differences in midshaft cross‐sectional area of prepubertal boys and girls matched for age, height, and weight, midshaft breadths were still retained in model creation, even though their overall contribution to models is generally lower than the distal or proximal breadths (Gilsanz et al, ; Nieves et al, ; Schoenau, Neu, Beck, Manz, & Rauch, ).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, several studies have shown the usefulness of intact long bones of upper and lower limbs 13,[30][31][32][33][34][35][36][37][38][39][40] for sex prediction in different parts of the world. In South Africa, local osteometric standards for sex estimation from skeletons have also been formulated from measurements of the skull [41][42][43] , long bones of the limbs [44][45][46][47][48][49][50][51][52] , sternum 53 , pelvis 54 and patella 55,56 . Similarly, measurements from the largest bones of the foot such as the talus 57,58 and calcaneus 59,60 have also been used for sex estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Forensic Anthropology methods for estimating the biological profile of unidentified remains are increasing during the last decades focusing on different anatomical elements, different populations and various statistical procedures which are heavily scrutinised to fulfil the expectations of the court. Amongst the basic biological features sex is the most studied with several methods marking high accuracies [1][2][3]. Scholars agree that most osteometric methods are population specific [4][5][6] with the exception of the pelvis [1,7].…”
Section: Introductionmentioning
confidence: 99%